Comparison of V̇O2-Kinetic Parameters for the Management of Heart Failure - Wagner, Jonathan; Niemeyer, Max; Infanger, Denis; Pfister, Otmar; Myers, Jonathan; Schmidt-Trucksäss, Arno; Knaier, Raphael (Frontiers in Physiology, 2021)
Objective: To analyse whether V̇O2-kinetics during cardiopulmonary exercise testing (CPET) is a useful marker for the diagnosis of heart failure and to determine which V̇O2-kinetic parameter distinguishes healthy participants and patients with heart failure (HF). Methods: 526 healthy participants and 79 patients with HF between 20 and 90 years of age performed a CPET. The CPET was preceded by a 3-minute low-intensity warm-up and followed by a 3-minute recovery bout. V̇O2-kinetics was calculated from the rest to exercise transition of the warm-up bout (on-kinetics), from the exercise to recovery transition following ramp test termination (off-kinetics) and from the initial delay of V̇O2 during the warm-up to ramp test transition (ramp-kinetics). Results: V̇O2 off-kinetics showed the highest z-score differences between healthy participants and patients with HF. Furthermore, off-kinetics were strongly associated with V̇O2peak. In contrast, ramp-kinetics and on-kinetics showed only minimal z-score differences between healthy participants and patients with HF. The best on- and off-kinetic parameters significantly improved a model to predict disease severity. However, there was no relevant additional value of V̇O2-kinetics when V̇O2peak was part of the model. Conclusions: V̇O2 off-kinetics appears to be superior for distinguishing patients with HF and healthy participants compared to V̇O2 on-kinetics and ramp-kinetics. If V̇O2peak can not be determined, V̇O2 off-kinetics provides an acceptable substitute. However, additional value beyond that of V̇O2peak can not be provided by V̇O2-kinetics.